Can the NHS successfully deliver its GP data extraction scheme?. (2nd September 2021) - Macdonald, Helen
Abstract : With the NHS's flagship GP data extraction programme facing further delays, Helen Macdonald examines what it is trying to achieve and the concerns surrounding it